Modern Physics Course in Online Learning: To What Extent are Students Successful in Learning? - Verawati, Ni Nyoman Sri Putu; Azmi, Irham (International Journal of Ethnoscience and Technology in Education, 2024)
The shift towards online education platforms has accelerated, highlighting the need for comprehensive evaluations of their effectiveness in delivering complex subjects like modern physics. This study aims to determine the success of students in an online modern physics course at Mataram University, focusing specifically on cognitive skills, conceptual understanding, and overall academic performance. Utilizing an experimental design, the research engaged 26 physics education students, aged 17 to 19, over a six-month academic period. The methods encompassed structured assessments through validated essay tests designed to measure distinct educational outcomes throughout the course duration. Findings reveal a broad variance in performance across measured metrics, with notable distinctions in students' abilities to grasp and apply complex physics concepts effectively. The results indicate that while online platforms can significantly enhance student learning outcomes when combined with interactive tools and effective engagement strategies, challenges such as limited hands-on experiences and variable technology access persist. These findings highlight the necessity for adaptive educational methods that cater to a diverse student body and underscore the potential of online education to extend beyond traditional classroom boundaries, enhancing learning through innovative approaches. This research contributes to the broader educational discourse by demonstrating that proactive adjustments in course design and delivery are essential to maximize the efficacy of online learning environments.